Parents’ Experiences in Assisting Elementary School Students in Using the Internet - Amining Rahmasiwi; Dewi Setyo Rini; Yessy Sulistyowati; Halimah (UIN Raden Mas Said Surakarta, 2022)
This cross-sectional survey seeks to explore parents’ experience in assisting elementary school students in using the internet during an emergency learning due to the Covid-19 pandemic. Data were collected through questionnaires. It was processed through descriptive qualitative data analysis. This current study involved 20 parents of elementary school students in Dukuh Mojolaban Sukoharjo. The results showed that 95% of parents limit children’s access to THE gadget by setting screen time, assisting the use of THE gadget, increasing interaction with children, and selecting appropriate programs or applications. Parents should assist their children in utilizing devices to reduce addiction and the negative impact of gadgets so that children are more focused on learning.